1990
DOI: 10.1007/bf00143681
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of immunoglobulin production stimulating factor derived from human B lymphoblastoid HO-323 cells

Abstract: An immunoglobulin (Ig) production stimulating factor (IPSF) for hybridomas was found in spent medium of the human B lymphoblastoid cell line, HO-323. The IPSF was purified by serial use of DEAE chromatography, ultrafiltration, gel filtration and HPLC-DEAE chromatography. Purified IPSF was estimated to be a 410 k macro molecule by gel filtration, and contained three types of isomers which were separated from each other by native polyacrylamide gel electrophoresis. All of the isomers were, however, assumed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Several methods of enhanced productivity of monoclonal antibody, which was achieved by increasing the cell concentration and/or the specific productivity of monoclonal antibody, were investigated by sev-eral researchers (Lee et al, 1994;Yamaguchi et al, 1997;Takahashi et al, 1994;Murakami et al, 1997). Productivity often depends on the components of culture media containing autocrine factors (Toyoda et al, 1990;Sugahara et al, 1991), extracts from plants and cells (Kim et al, 1993), and other components (Mochizuki et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of enhanced productivity of monoclonal antibody, which was achieved by increasing the cell concentration and/or the specific productivity of monoclonal antibody, were investigated by sev-eral researchers (Lee et al, 1994;Yamaguchi et al, 1997;Takahashi et al, 1994;Murakami et al, 1997). Productivity often depends on the components of culture media containing autocrine factors (Toyoda et al, 1990;Sugahara et al, 1991), extracts from plants and cells (Kim et al, 1993), and other components (Mochizuki et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors termed immunoglobulin production stimulating factor (IPSF) were discovered in cell extracts or culture medium. IPSF-I was discovered in culture medium from a human lymphoblastoid cell line HO-323 [1], and IPSF-II was purified from cell lysate of human Burkitt's lymphoma, Namalwa cells [2,3]. The previous data revealed that the Namalwa cell lysate contained two IPSF active substances, IPSF-Ikx and -II,8, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that there are substances termed Ig production stimulating factor (IPSF) which enhance Ig production by hybridomas and lymphocytes. IPSF-I purified from culture medium of human lymphoblastoid cell line, HO-323 was a 410 kDa macro-protein (Toyoda et al, 1990). IPSF-II was found in cell extracts of Namal-wa cells (Sugahara et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%